Prevalence of dental caries among children in Indonesia: a systematic review and meta-analysis of observational studies - Hasan, Faizul; Yuliana, Lia Taurussia; Budi, Hendrik Setia; Ramasamy, Rajesh; Ambiya, Zilzala Irqon; Ghaisani, Anindya Marsa (Elsevier, 2024)
Objective: The prevalence of dental caries among children in Indonesia remains unclear. Therefore, we aimed to provide an updated assessment of this prevalence while also investigating the influence of patient characteristics and methodological factors. Design: We performed a systematic review and meta-analysis, including searches of PubMed, Cochrane Library, and Embase from inception to August 24, 2023. We included 8840 participants in 27 studies reporting the prevalence of dental caries among Indonesian children. Results: The overall prevalence of dental caries was 76 % (95 % confidence interval: 71%–81 %). Studies in which decay-missing-filled teeth (DMFT) criteria were used to diagnose dental caries were significantly more prevalent than studies using non-DMFT criteria (78 % vs. 64 %, P <0.05). No significant moderators were identified for the study subgroup based on study origin (Jakarta vs. non-Jakarta) or comorbidity status (comorbidity vs. no comorbidity). Owing to incomplete reporting of variables, metaregression analysis could not be conducted for continuous variables, such as age and male percentage. Conclusions: The prevalence of dental caries among Indonesian children remains notably high, showing consistency across Jakarta-based studies and non-Jakarta studies. Initiating dental caries prevention and health promotion campaigns is imperative, focusing on the critical importance of early detection.